In vivo and in vitro anti-inflammatory and pro-osteogenic effects of citrus cystatin CsinCPI-2 - Leguizamón, Natalia Da Ponte [UNESP]; Rodrigues, Elisandra Marcia [UNESP]; de Campos, Michel Leandro; Nogueira, Andressa Vilas Boas [UNESP]; Viola, Kennia Scapin [UNESP]; Schneider, Vanessa Karine; Neo-Justino, Daniela Morilha; Tanomaru-Filho, Mario [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Henrique-Silva, Flavio; Soares-Costa, Andrea; Faria, Gisele [UNESP]; et al. (Elsevier, 2019)
Cystatins are natural inhibitors of cysteine peptidases. Recently, cystatins derived from plants, named phytocystatins, have been extensively studied. Among them, CsinCPI-2 proteins from Citrus sinensis were identified and recombinantly produced by our group. Thus, this study described the recombinant expression, purification, and inhibitory activity of this new phytocystatin against human cathepsins K and B and assessed the anti-inflammatory effect of CsinCPI-2 in vitro in mouse and in vivo in rats. In addition, the pro-osteogenic effect of CsinCPI-2 was investigated in vitro. The inflammatory response of mouse macrophage cells stimulated with P. gingivalis was modulated by CsinCPI-2. The in vitro results showed an inhibitory effect (p < 0.05) on cathepsin K, cathepsin B, IL-1β, and TNF-α gene expression. In addition, CsinCPI-2 significantly inhibited in vivo the activity of TNF-α (p < 0.05) in the blood of rats, previously stimulated by E. coli lipopolysaccharide (LPS). CsinCPI-2 had a pro-osteogenic effect in human dental pulp cells, demonstrated by the increase in alkaline phosphatase (ALP) activity, deposition of mineralized nodules, and the gene expression of the osteogenic markers as bone morphogenetic protein 2 (BMP-2), runt-related transcription factor 2 (Runx-2), ALP, osteocalcin, and bone sialoprotein (BSP). These preliminary studies suggested that CsinCPI-2 has a potential anti-inflammatory, and at the same time, a pro-osteogenic effect. This may lead to new therapies for the control of diseases where inflammation plays a key role, such as periodontal disease and apical periodontitis.
Keywords: Cathepsins; Cystatins; Cysteine proteinases; Cytokines